PENGUATAN KULTUR SEKOLAH UNTUK MEWUJUDKAN PENDIDIKAN RAMAH ANAK - Wiwik Kusdaryani; Iin Purnamasari; Aries Tika Damayani (Jurnal Cakrawala Pendidikan, 2016)
Abstrak: Penelitian bertujuan mengkaji konsep kultur sekolah, menganalisis konsep pendidikan ramah anak, dan penguatan kultur sekolah dalam mewujudkan pendidikan ramah anak. Jenis penelitian kualitatif dengan metode fenomenologi, yang dilakukan di SDN Pingit 01 Kecamatan Pringsurat Kabupaten Temanggung. Teknik pengumpulan data dilkukan dengan wawancara, pengamatan, dan analisis dokumen, sedang analisis data dengan teknik deskreptif kualitatif. Hasil penelitian menunjukkan bahwa: 1) konsep kultur sekolah meliputi beberapa modal budaya sekolah berdasarkan kebiasaan warga sekolah dan tertuang dalam visi misi, tata tertib, 8 budaya disiplin guru, dan 10 budaya malu siswa; 2) konsep pendidikan ramah anak ditemukan dalam sikap guru terhadap siswa yang memberikan perhatian, perlindungan, serta berperan sebagai informator, mediator, motivator dan fasilitator dalam meningkatkan prestasi akademik dan nonakademik, serta metode pembelajaran perlu ditingkatkan; 3) penguatan kultur sekolah dalam mewujudkan pendidikan ramah anak dikembangkan berdasarkan berbagai kebiasaan positif sekolah. Kata Kunci: kultur, sekolah, pendidikan ramah anak STRENGTHENING THE SCHOOL CULTURE TO REALIZE THE CHILD-FRIENDLY EDUCATION Abstract:This study was aimed to examine the concept of the school culture, to analyze the child-friendly education, and to strengthen the school culture to realize the child-friendly education. This study used the phenomenology method, carried out ini SDN Pingit 01, Pringsurat, Temanggung. The data were collected using interviews, observations, and the document analysis. The data were analyzed using the qualitative descriptive analysis. The findings showed that: 1) the concept of school culture involved several school culture capitals based on the habit of the school members and this was conceptualized in the vision, mission, school regulations, 8 teachers’ discipline cultural items, and 10 students’ cultural items of being ashamed when doing something bad; 2) the concept of child-friendly education could be found in the teachers’ attitude towards the students by giving attention and protection, by becoming informants, mediators, motivators, and facilitators to improve the students’ academic and non-academic learning achievement; the teaching methods needed to be improved; 3) the strengthening of the school culture to realize the child-friendly education was developed based on several positive habits done in the school. Keywords: culture, schools, child-friendly education